Ativação neuronal de circuitos funcionais do cerebelo em funções motoras e não motoras de camundongos - Prati, José Mário (Universidade Federal de São Carlos, 2021)
The cerebellum is a brain structure involved in the control of balance, movement and the acquisition of motor skills. With scientific and technological advances, studies have shown that the cerebellum also participates in non-motor functions, such as emotional control, memory and language. However, it is not yet known which cerebellar areas and which circuits are predominantly activated in different functions. The aim of this study was to analyze the neuronal activation of cerebellar areas and other brain structures (hippocampus, amygdala and medial prefrontal cortex) after exposure to the behavioral models of RotaRod and the Inhibitory Avoidance model, and to develop possible neuronal circuits for the possible functions motor and non-motor. For that, naive, male Swiss Albino mice, weighing between 25 and 35g, were used. For the behavioral evaluation, the animals were obtained under three conditions: home cage/control; Inhibitory Avoidance, emotional memory model; and Rota Rod that assesses motor performance and motor learning. In condition 1, animals remained in the home-cage; in condition 2 they were exposed to the Inhibitory Avoidance protocol for 2 days; and in condition 3 to RotaRod for 3 days. After the last exposure to the apparatus, the animals were euthanized, and then perfused with Paraformoldehyde and its brain extracted and sectioned for immunofluorescence analysis of c-Fos protein from the structures. Images of the brain structures were captured and their neuronal activation was analyzed microscopically. One-way ANOVA analysis of variance was used, followed by Tukey's post-hoc test. There was no significant difference in the expression of c-Fos in lobe VI of the cerebellum between the different conditions. In contrast, there was a difference in the expression of c-Fos in the basolateral amygdala, infra-limbic cortex and pre-limbic cortex, which are brain structures relevant to emotional processes, in the exposure of animals to the assessment apparatus. The Pearson Correlation Coefficient test demonstrated a positive correlation between the variables of the structures related to emotional processes. We concluded that there was no significant difference in the expression of c-Fos in lobe VI of the cerebellum in the exposure of animals to the evaluation apparatus. In contrast, there was a difference in the expression of c-Fos in the other brain structures relevant to emotional processes in the exposure of animals to the assessment apparatus.
Neuronal activation of cerebellum functional circuits in non-motor and motor functions of mice
Keywords: Ativação neuronal; Cerebelo; Funções motoras; Funções não motoras; c-Fos; Neuronal activation; Cerebellum; Motor functions; Non-motor functions; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL